Risk of paralytic and diarrhetic shellfish poisoning associated with the consumption of bivalves from north Mumbai creek - Shahi, Neetu; Nayak, B B; Mallik, Sumanta Kumar (Indian Journal of Fisheries, 2016)
Risk assessment study with respect to shellfish toxins of algal origin was carried out in coastal villages of Mumbai. Live Meretrix sp. was collected monthly during November 2005 - December 2006 from Manori creek. Analysis of crude toxins by mouse bioassay (MBA) was done for paralytic shellfish poisoning (PSP) and diarrhetic shellfish poisoning (DSP) and exposure assessment was done by survey in five fishing villages. Level of PSP and DSP toxins were below the detectable limit. Survey revealed that 14% had diarrhea, and other stomach related ailments following consumption of clams. Significant number of PSP causing dinoflagellates Alexandrium minutum, Alexandrium acatenella, Alexandrium tamarense, Gymnodinium nagasakiense and Pyrodinium bahamense were present in coastal waters. Similarly DSP causing dinoflagellates Dinophysis norvegica, Dinophysis caudata, Dinophysis rotundata and Dinophysis acuminata were also observed at <120 cells l-1 the low toxicity level revealed by MBA and relatively low consumption level by the local communities indicate that the shellfish of that area pose low risk to the consumers. The survey also revealed no reported human death due to PSP and very low incidences of symptoms of DSP.